Catalytic Bio‐Supramolecular Photochirogenesis: Batch‐Operated Enantiodifferentiating Photocyclodimerization of 2‐Anthracenecarboxylate with Human Serum Albumin. Issue 11 (5th June 2013) - Nishijima, Masaki; Kato, Hanako; Yang, Cheng; Fukuhara, Gaku; Mori, Tadashi; Araki, Yasuyuki; Wada, Takehiko; Inoue, Yoshihisa
<x xml:space="preserve">Abstract</x> Chiral induction: Catalytic bio‐supramolecular photochirogenesis is achieved for the enantiodifferentiating [4+4] photocyclodimerization of 2‐anthracenecarboxylate by repeatedly using human serum albumin (HSA) as a chiral mediator; the original high enantiomeric excess values (up to 80–90 %) are preserved.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>